Exploring Schiff Bases as Promising Alternatives to Traditional Drugs in the In Silico Treatment of Anti-Leishmaniasis as Trypanothione Reductase Inhibitors - Diego R. Peixoto; Carlos S. H. Shiraishi; Rui M. V. Abreu; Osmair V. Oliveira; José D. dos Santos (Proceedings)
Leishmaniasis, caused by the protozoan Leishmania spp. and transmitted by sandflies, affects 2 million people worldwide yearly and is recognized as a global problem by the WHO. Current treatments, including amphotericin B, Pentamidine, and Glucantime, show limited efficacy and serious side effects. Trypanothione reductase is a promising protein target for developing new promising drugs against Leishmaniasis. This study explores Schiff base compounds as potential alternatives to current treatments by inhibiting trypanothione reductase. Thirty-nine structures from the PubChem database were selected and analyzed using AutoDock Vina 1.1, an in silico molecular docking tool. Promising Schiff base candidates, indicated as compound 21 (3-Quinolinamine, N-(2-quinolinylmethylene)-, compound 24 (1,3-Bis[(E)-(2-Amino-4-Ethyl-5-Hydroxy-Phenyl)Methyleneamino]Urea, and compound 39 (Naphtaldehyde disulfide Schiff base), exhibited significant inhibitory binding affinity against trypanothione reductase, outperforming commercial inhibitors. Therefore, the present study proposes alternative Schiff base compounds for treating Leishmaniasis.